2012
DOI: 10.4314/ajtcam.v9i4.6
|View full text |Cite
|
Sign up to set email alerts
|

Why HIV Positive Patients on Antiretroviral Treatment and/or Cotrimoxazole Prophylaxis Use Traditional Medicine: Perceptions of Health Workers, Traditional Healers and Patients: A Study in Two Provinces of South Africa

Abstract: The study explored the perceptions, knowledge and attitudes of patients, health workers and traditional healers about the use of traditional medicine and Anti Retroviral Therapy (ART). The study explored the perceptions, knowledge and attitudes of patients, health workers and traditional healers about the use of traditional medicine and Anti Retroviral Therapy (ART), using an exploratory qualitative design in two provinces of South Africa: an urban township health facility in the Western Cape, and a rural dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 17 publications
0
29
1
Order By: Relevance
“…This is despite the fact that health information is received by participants mostly from conventional healthcare practitioners. Such non-disclosure of THM use is not peculiar to this study, and has been reported in other studies [37, 39, 40]. However, this is in contrast to findings from studies conducted in Australia [27] and the United States [20], where older women disclosed CAM use to their healthcare providers.…”
Section: Discussioncontrasting
confidence: 70%
“…This is despite the fact that health information is received by participants mostly from conventional healthcare practitioners. Such non-disclosure of THM use is not peculiar to this study, and has been reported in other studies [37, 39, 40]. However, this is in contrast to findings from studies conducted in Australia [27] and the United States [20], where older women disclosed CAM use to their healthcare providers.…”
Section: Discussioncontrasting
confidence: 70%
“…Previous studies on the use of TAM in the context of HIV treatment have posited TAM and allopathic medicine as parallel, sometimes polarised approaches whose use depends on multiple factors like availability and access to treatment (Littlewood & Vanable, 2011), and have called for further examination into the motivations for TAM use (Puoane, Hughes, Uwimana, Johnson, & Folk, 2012). The findings here suggested implicit cultural motivators for TAM use that were independent of a patient’s HIV-related health-seeking behaviour(s).…”
Section: Discussionmentioning
confidence: 99%
“…The study design addressed a noted gap in literature by directly involving traditional healers. Other studies (Graham et al, 2012; Mngqundaniso & Peltzer, 2008) have engaged traditional healers and allopathic medical practitioners, but to date and to the best of our knowledge, few in South Africa have engaged doctors, allopathic medical health care providers, and traditional healers in the same study (Puoane et al, 2012). The perspectives of traditional healers contributed immensely to the findings and themes revealed here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have indicated that THPs lack the biomedical skills and knowledge to diagnose and treat HIV [34,35,44], THPs who are trained in HIV/AIDS have been used to educate patients about the causes and consequences of HIV, and have provided physical and psychosocial community-based HIV care [19,45–47]. A quantitative study conducted among patients consulting THPs in the context of HIV/AIDS found that PLHIV did so owing to several complex health situations [28].…”
Section: Introductionmentioning
confidence: 99%